Germinación de semillas de la especie Schizolobium parahybum (vell.) Blake, (pachaco) con aplicación de tratamientos pre germinativos en diferentes tipos de subtratos, Puerto Almendra, Iquitos, Loreto-2013 - Escudero Linares, Paul Enrique (2013)
The research was carried out at the Fundo Puerto Almendras, owned by the Faculty of Forestry Engineering of the National University of the Peruvian Amazon. The fundamental objective of the research was to determine the degree of influence of pre-germination treatments and types of substrate of the seeds of the species Schizolobium parahybum (vell.) Blake, pachaco in the germination process. The method used was deductive, inductive, statistical descriptive. Among the most important results obtained was the identification of the species through the support of the Hebarium Amazonense of the National University of the Peruvian Amazon, confirming that the genus and species was Schizolobium parahybum belonging to the Fabaceae family, with the common name pachaco, likewise determined through the Analysis of variance that Pi value was less than 0.05 in the case of treatments a and b, therefore there is a significant difference, that is, factors A and b are different because the levels are of heterogeneous performance compared to each other, so it is necessary to perform the tukey test, where it was found that B2 is significant with B1 and B0.